Treatment of venous thromboembolism – effects of different therapeutic strategies on bleeding and recurrence rates and considerations for future anticoagulant management - Hass Bastian (Thrombosis Journal, 2012)
Abstract Effective treatment of venous thromboembolism (VTE) strikes a balance between prevention of recurrence and bleeding complications. The current standard of care is heparin followed by a vitamin K antagonist such as warfarin. However, this option is not without its limitations, as the anticoagulant effect of warfarin is associated with high inter- and intra-patient variability and patients must be regularly monitored to ensure that anticoagulation is within the narrow target therapeutic range. Several novel oral anticoagulant agents are in the advanced stages of development for VTE treatment, some of which are given after an initial period of heparin treatment, in line with current practice, while others switch from high to low doses after the initial phase of treatment. In this review we assess the critical considerations for treating VTE in light of emerging clinical data for new oral agents and discuss the merits of novel treatment regimens for patients who have experienced an episode of deep vein thrombosis or pulmonary embolism.